1983
DOI: 10.1113/jphysiol.1983.sp014840
|View full text |Cite
|
Sign up to set email alerts
|

Electrical activities of the muscle layers of the canine colon.

Abstract: SUMMARY1. The spontaneous electrical and mechanical activities of the circular and longitudinal muscle layers of the canine colon were studied.2. The smooth muscle cells of the circular muscle layer exhibited regular, omnipresent myogenic slow-wave activity at a frequency ranging from 4 to 7 c/min. With intracellular micro-electrodes, the slow-wave amplitude was 21-38 mV and its duration 3-6 sec. The 'resting' membrane potential was -60 to -76 mV. Some slow waves had superimposed spike bursts on their peak dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
35
2

Year Published

1986
1986
1997
1997

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(40 citation statements)
references
References 20 publications
3
35
2
Order By: Relevance
“…In contrast to the slow waves in the small intestine and stomach, which appear to be generated within or near the longitudinal muscle and propagate into the circular muscle layer (Bortoff, 1965;Kobayashi, Nagai & Prosser, 1966; Connor, Prosser & Weems, 1974;Connor, Kreulen, Prosser & Weigel, 1977; Bauer, Publicover & Sanders, 1985), slow waves of colonic circular muscle appear to be generated in the circular layer (Christensen et al 1969;Caprilli & Onori, 1972;El-Sharkawy, 1983;Huizinga et al 1983) adjacent to the submucosal border (Caprilli & Onori, 1972;Chambers et al 1984). Unlike the small bowel and stomach, the longitudinal and circular muscles of the colon exhibit different electrical activities (Christensen et al 1969;El-Sharkawy, 1983;Huizinga et al 1983). Circular muscle generates slow wave activity as described above, whereas longitudinal muscles of the dog and pig colon generate pre-potentials and action potentials that are not associated with slow waves but appear to be dependent on external stimuli such as stretch or acetylcholine (El-Sharkawy, 1983;Huizinga et al 1983).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to the slow waves in the small intestine and stomach, which appear to be generated within or near the longitudinal muscle and propagate into the circular muscle layer (Bortoff, 1965;Kobayashi, Nagai & Prosser, 1966; Connor, Prosser & Weems, 1974;Connor, Kreulen, Prosser & Weigel, 1977; Bauer, Publicover & Sanders, 1985), slow waves of colonic circular muscle appear to be generated in the circular layer (Christensen et al 1969;Caprilli & Onori, 1972;El-Sharkawy, 1983;Huizinga et al 1983) adjacent to the submucosal border (Caprilli & Onori, 1972;Chambers et al 1984). Unlike the small bowel and stomach, the longitudinal and circular muscles of the colon exhibit different electrical activities (Christensen et al 1969;El-Sharkawy, 1983;Huizinga et al 1983). Circular muscle generates slow wave activity as described above, whereas longitudinal muscles of the dog and pig colon generate pre-potentials and action potentials that are not associated with slow waves but appear to be dependent on external stimuli such as stretch or acetylcholine (El-Sharkawy, 1983;Huizinga et al 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that canine, feline, and porcine colonic circular smooth muscle cells exhibit rhythmic, myogenic depolarizations and repolarizations of the membrane potential or 'slow waves' (Christensen, Caprilli & Lund, 1969;El-Sharkawy, 1983;Huizinga, Diamant & El-Sharkawy, 1983;Chambers, Kingma & Bowes, 1984). In contrast to the slow waves in the small intestine and stomach, which appear to be generated within or near the longitudinal muscle and propagate into the circular muscle layer (Bortoff, 1965;Kobayashi, Nagai & Prosser, 1966; Connor, Prosser & Weems, 1974;Connor, Kreulen, Prosser & Weigel, 1977; Bauer, Publicover & Sanders, 1985), slow waves of colonic circular muscle appear to be generated in the circular layer (Christensen et al 1969;Caprilli & Onori, 1972;El-Sharkawy, 1983;Huizinga et al 1983) adjacent to the submucosal border (Caprilli & Onori, 1972;Chambers et al 1984).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Between species the frequency of slow waves shows some variation; for example in the dog the frequency is about 5 cycles min-' (El-Sharkawy, 1983;Smith et al 1987 a, b) whereas in the pig the frequency is 0-5-3 5 cycles min-' (Huizinga et al 1983. Action potentials may or may not accompany the slow waves.…”
Section: Introductionmentioning
confidence: 99%
“…In colonic longitudinal muscle of several species including the guinea-pig, dog, pig and human, the.application of stretch appears to promote the onset of membrane potential oscillations. The onset of oscillatory activity appears to be controlled by both myogenic and neurogenic mechanisms (Biilbring, 1955;Gillespie, 1962;El-Sharkawy, 1983;Huizinga, Diamant & El-Sharkawy, 1983;Huizinga, Stern, Chow, Diamant & El-Sharkawy, 1985;Huizinga, Chow, Diamant & El-Sharkawy, 1987;Smith et al 1987 a).…”
Section: Introductionmentioning
confidence: 99%